Improving the growth of pea plant by biochar–polyacrylamide association to cope with heavy metal stress under sewage water application in a greenhouse - Naveed, Muhammad; Fatima, Maryum; Naseem, Zainab; Ahmad, Zulfiqar; Gaafar, Abdel-Rhman Z; Shabbir, Mubashra; Farooq, Qurrat ul Ain; Hodhod, Mohamed S.; Khan, Muhammad Imran; Shahid, Dua; Mustafa, Adnan (Frontiers in Environmental Science, 2024)
Sewage water is extensively used for irrigation, serving as a valuable resource for plant growth to enhance agricultural productivity. However, this practice also results in a significant accumulation of heavy metals in the soil, posing potential environmental and health concerns. A study was designed to evaluate the combined effect of amendments on heavy metal immobilization in soil and improved growth and yield of pea plants. For this, soil for each treatment was mixed with biochar (BC) (1% w/w), polyacrylamide (PAM) (0.5% w/w), as well as applied in combination. Pea plants were irrigated with tap water (TW), sewage water (SW), and tap + sewage water (TW+SW). A factorial design was applied to analyze data statistically. The combined application of biochar and polymer showed a positive response by significantly enhancing the plant growth parameters (39-84%), physiological attributes (67-69%) and reducing Cd (56%) and Cr (65%) concentration in soil applied with SW and TW+ SW. Moreover, treatment with a combined application of BC and PAM significantly reduced Cd concentrations by 43% in roots, 50% in shoots, and 91% in grains. Similarly, Cr concentrations were reduced by 51% in roots, 51% in shoots, and 94% in grains compared to the control. Overall, our results indicate reduced bioaccumulation and health risks associated with potentially toxic elements (PTE), supporting the application of polymer and biochar for irrigating pea plants with TW+SW. Leveraging the combined benefits of polymer and biochar amendments appears to be an effective strategy to remediate PTE-contaminated soil, thereby increasing plant growth and yield.